Transformasi Pondok Pesantren (Upaya Merawat Tradisi dan Modernisasi Sistem Pesantren di Era Disrupsi) - Mufron, Ali (Tarbawi: Journal of Islamic Education, 2020)
This research is motivated by the challenges of Islamic boarding schools in the midst of a dynamic global movement that requires pesantren to adapt quickly and carry out transformation, but on the other hand they are still able to maintain tradition, culture, and culture as distinctions that become the distinction of other educational institutions. The method used by the authors in this study is the literature, through primary data reading the latest books. This study involves colleagues, namely lecturers of Islamic education management from various campuses, with the steps: testing the text through discussion, criticism, suggestions, improvements, and finalization. Based on the results of the study it can be concluded that the change effort in Islamic boarding schools to be more structured systematically pesantren should be able to meet eight national education standards with the hope that out and out come boarding schools can answer global challenges and have multidimensional intelligence.Keywords: Transformation, Pesantren, Tradition, Modernization